COMMENT ON THE TAU DECAY PUZZLE - Escobar, C. O.; Peres, OLG; PLEITEZ, V; Funchal, R. Z. (Editions Physique, 1993)
We analyse the current data on tau-lepton decays and show that they are consistent with the standard model.